Peran dan Fungsi Mahkamah Konstitusi Dalam Pembangunan Politik Hukum Pemerintahan Daerah - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2012)
After the shift of authority in the dispute settlement of Regional Head Election from Supreme Court to Constitutional Court, and the authority to evaluate the regulations of law of Constitutional Court, there is high public expectation on the role and functions of the Constitutional Court in the dispute settlement in Regional Head Election. This research discusses the problems on, first, the role and functions of Constitutional Court in the establishment of regional government law politics in Indonesia. Second the legal implications of the decision of Constitutional Court on the regional government governance. This research is a normative legal research using case study method. The result of the research concludes that, first, the role and functions of Constitutional Court is very significant, especially through the authority to evaluate the regulations of law and on the dispute settlement governing the regional head election. Second, the decision of Constitutional Court has given legal implication to the regional head election governance, that is the follow-up action by the lawmakers (Government and Legislative) by revising several particular provisions which has been annulled.